Auscultatory characteristics of normally functioning Lillehei-Kaster, Björk-Shiley, and St Jude heart valve prostheses. Issue 4 (April 1986) - Kupari, M; Harjula, A; Mattila, S
Abstract : Auscultatory and echocardiographic and phonocardiographic studies were performed on 26 patients who had a total of 11 Lillehei-Kaster, 16 Björk-Shiley, and 18 St Jude heart valve prostheses functioning normally in the aortic or mitral positions or both. With all types and positions of prostheses a distinct closing sound was always detected. It was frequently heard in two parts which, according to echocardiographic and phonocardiographic studies, resulted from the onset and completion of the valve closure. An opening sound could be heard from all Björk-Shiley and St Jude valves but from only four of the 11 Lillehei-Kaster valves. The opening sounds due to mitral prostheses consisted of two to three closely spaced clicks detected as a faint early diastolic crackle on auscultation. Echocardiography with phonocardiography indicated that they were related to the onset and termination of the disc opening excursion. In the aortic position the valves always produced early to mid-systolic murmurs, and a soft early diastolic murmur was also heard in seven of 23 patients. A mid-diastolic rumble was heard in 12 of 22 patients with mitral prostheses. Normally functioning tilting disc valve prostheses produce characteristic auscultatory findings, and familiarity with these findings will be useful in clinical evaluation of patients with these prostheses.